THE INFLUENCE OF FRUGALITY ON SUBJECTIVE WELL-BEING WITH RELIGIOSITY AS A MODERATOR VARIABLE: A STUDY ON EARLY ADULT ONLINE SHOPPERS - Gloria Meydelina; Wahyuni Kristinawati; Adi Setiawan (Pusat Publikasi Nusantara, 2025)
This study aims to examine the influence of frugality on subjective well-being (SWB) in early adult online shoppers, with religiosity as a moderator variable. The study participants consisted of men and women aged 18-40 years who are online shoppers in Indonesia. The hypothesis test was carried out using the Multiple Linear Regression technique, and the results of this study showed that the results showed that a positive relationship was found between the three variables. The results of the study also showed that religiousosis positively moderated the relationship between the variables ( = 0.073, p 0.10). In addition, it was found that the relationship was negatively correlated with the two variables (P 0.05). In conclusion, it is suggested that online shoppers can implement a lifestyle of simplicity by making a list of shopping priorities, comparing prices between platforms, and considering the use value of products before making purchases.